Fixing what ain't broke. Issue 2 (8th April 2016) - Marks, Jonathan
Abstract : With its subtitle 'Prescriptivism and Language History', Fixing English encompasses two senses of 'fixing': firstly, attempting to freeze the language at a particular historical moment and prevent it from changing further and, secondly, attempting to improve it and repair it of its faults and shortcomings.